Electrodeposited Conducting Polyaniline Nanowire Arrays Aligned on Carbon Nanotubes Network for High Performance Supercapacitors and Sensors. (1st May 2016) - Hui, Ni; Chai, Fenglian; Lin, Peipei; Song, Zhiling; Sun, Xiaotian; Li, Yinan; Niu, Shuyan; Luo, Xiliang
Abstract: Conducting polymer polyaniline (PANI) nanowire arrays were electrochemically in situ synthesized on the surface of glassy carbon electrodes, which were modified with self-assembled multi-walled carbon nanotubes (CNTs) networks. The ordered PANI nanowire arrays and CNTs networks were integrated to create 3D nanostructured PANI/CNTs composites. Owing to their unique microstructure and conductivity, the PANI/CNTs nanocomposite exhibited excellent electrical properties such as remarkable supercapacitor performance and catalytic activity toward nitrite electrochemical reduction. It was found that the PANI/CNTs nanocomposite was capable of delivering high specific capacitance and showed excellent cycling stability. Moreover, it could be utilized as an electrochemical sensor for the detection of nitrite, with an outstanding sensitivity, low detection limit (6.1 μM, a signal to noise ratio of 3) and a fast response time of less than 5 s.